Analyzing Ethical Practices and Sustainability in Indonesian Real Estate: A Comprehensive Business Study - Setiono, Bambang; Handayani, Sri; Biantara, Dheny (School of Accountancy, University of Agung Podomoro, 2024)
This study examines the performance of companies in business ethics and sustainability management within Indonesia's real estate industry using the Accounting for Business Ethics and Sustainability (A4BES) framework. Ethical and sustainability leadership is categorized into conventional, follower, transitional, and modern groups based on A4BES scores and stakeholder interest harmonization. Findings reveal no companies classified as followers or modern. On average, companies achieve 16.94% of the maximum A4BES score, or 25.75 out of 152 points. CTRA and DILD are the frontrunners, both scoring 67 (44.08%). DILD demonstrates superior leadership with better stakeholder harmonization: 43.28% for employee interests, 7.46% for customer interests, 13.43% for community interests, and 35.82% for environmental interests. This study provides insights into ethical and sustainability leadership and introduces an outcome-based approach for evaluating firm performance, encouraging the integration of ethical and sustainability decisions into strategic and operational practices.